Biomass Mediated Synthesis of ZnO and ZnO/GO for the Decolorization of Methylene Blue under Visible Light Source - Salma, Ahmed Al-Zahrani; Khalid, Umar; Saleh Ali, Tweib; Jebrel Abdeljawad, M. Rashd; Saima, Khan Afridi; Showkat, Ahmad Bhawani; Ahmed, Al Otaibi; Najat, Masood; Dorsaf, Mansour; Anish, Khan; Manikandan, Ayyar (MDPI, 2023)
: In this study, zinc oxide (ZnO) as well as ZnO/GO (zinc oxide/graphene oxide) were successfully synthesized. The Carica papaya leaf extract was used to synthesize ZnO and oil palm empty fruit bunch biomass to obtain graphene, which was further used to obtain graphene oxide. The samples were characterized through a variety of analytical methods such as scanning electron microscopy, transmission electron microscopy, X-ray diffraction analysis, Fourier transform infrared spectroscopy and UV–Visible spectroscopy in order to understand their morphology, size, structural phase purity, functional groups and optical properties. Various peaks such as O-H, Zn-OH and Zn-O were found in the case of ZnO. Some additional peaks, such as C-C and C=C, were also been detected while analyzing the sample by Fourier-transform infrared spectroscopy. The results of the XRD and SEM studies demonstrated that the synthesized material shows the crystalline nature of the substance in the case of ZnO, and the crystallinity decreases for ZnO/GO. The average crystallite size was found to 80.0 nm for ZnO and 74.0 nm for ZnO/GO. Further, a red shift was shown in the case of ZnO/GO, which was indicated by the UV–Vis absorption spectrum. In the TEM analysis, the particles were shown to be nanosized. For instance, the highest number of particles was found in the range of 100 to 120 nm in the case of ZnO, while 80–100 nm sized particles were found for ZnO/GO. Using synthesized ZnO and ZnO/GO, the decolorization of methylene blue was found to be 64% and 91%, respectively.